Les pays d'Afrique australe et orientale conviennent d'une approche commune - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Le COMESA et la SADC sont formellement convenus d'adopter une position ...